Digitalisasi Kantor Desa : Solusi Cerdas Meningkatkan Pelayanan Dan Pemberdayaan Ekonomi Masyarakat Desa Silo Bonto Kabupaten Asahan - Rahayu, Elly; Herman Saputra; Adi Prijuna Lubis; Waode Aminah Andella (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: This PkM activity aims to provide new knowledge and insights for Silo Bonto Village officials on the benefits of digitalizing the village, improving village services, and empowering the community's economy. Silo Bonto Village has a population of 6,387 people spread across 11 hamlets. The majority of the people in Silo Bonto Village, Silau Laut District, Asahan Regency, are farmers who cultivate coconut and oil palm plantations. The Silo Bonto Village Office has a village application, but it has not been utilized, the problems that arise are the absence of skilled human resources in the village office who can run open desa application, secondly, the limited village budget to fund technological infrastructure. Another problem is that there is community resistance to the use of technology in the village service system. This activity aims to help villages find solutions to existing problems, one of which is providing knowledge and skills on how digitalization can make village services and economic empowerment more efficient and improved. The PkM activity was attended by village officials hamlet heads and representatives of the community totaling 24 people. The method used is Community Base-Participatory Research (CBPR). The results of activity, in addition to the implementation of this PkM activity, there has also been a transfer of knowledge from the implementer to the participants of the socialization about Village Office Digitalization: Smart Solutions to Improve Services and Community Economic Empowerment. Keywords: village; digitalization; open desa;economic empowerment; improving village services Abstrak: Kegiatan PkM ini bertujuan untuk memberikan pengetahuan dan wawasan baru bagi aparat Desa Silo Bonto manfaat digitalisasi desa bagi peningkatan layanan desa dan pemberdayaan ekonomi masyarakat. Desa Silo Bonto yang berpenduduk 6387 jiwa yang tersebar di 11 dusun. Mayoritas masyarakat Desa Silo Bonto Kecamatan Silau Laut Kabupaten Asahan adalah petani perkebunan kelapa dan kelapa sawit. Kantor Desa Silo Bonto memiliki aplikasi desa, namun belum dimanfaatkan, permasalahan yang muncul adalah belum adanya SDM terampil di kantor desa yang mampu menjalankan aplikasi Open Desa, kedua terbatasnya anggaran desa untuk mendanai infratruktur teknlogi. Permasalahan lainnya adalah ada resisitensi masyarakat dalam penggunaan teknologi dalam sistem pelayanan desa. Kegiatan ini bertujuan untuk membantu desa dalam mencari solusi dari permasalahan yang ada, ssalah satunya memberikan pengetahuan dan keterampilan bagaimana digitalisasi mampu mengefisienkan dan meningkatkan layanan dan pemberdayaan ekonomi desa. Kegiatan Pk Mini dihadiri oleh apparat desa dan kepala dusun serta perwakilan Masyarakat yang berjumlah 24 orang. Metode yang digunakan adalah Community Base-Partisipatory Research (CBPR). Hasil kegiatan, selain terlaksananya kegiatan PkM ini juga telah terjadi transfer ilmu dari pelaksana ke peserta sosialisasi tentang Digitalisasi Kantor Desa: Solusi Cerdas Meningkatkan Pelayanan Dan Pemberdayaan Ekonomi Masyarakat. Kata kunci: desa; digitalisasi; open desa; pemberdayaan ekonomi; peningkatan layanan desa